Suppression of Pain by Exposure of Acupuncture Points to Polarized Light - Yuri P Limansky; Zinaida A Tamarova; Sergiy A Gulyar (Pain Research and Management)
BACKGROUND: According to clinical studies, the stimulation of acupuncture points (APs) by a variety of methods (eg, needles, pressure, etc) is an effective method for the treatment of many pain syndromes. However, no experimental proof exists showing that the exposure of APs to low-intensity incoherent polarized (P) light evokes an analgesic affect.